Dynamics of Saltwater Intrusion Into Coastal Freshwaters in the California Central Coast - Lauren N. Kim; Casey Meusel; Rusty Barker; Brian Lockwood; Mark Strudley; Dane Behrens; Mara M. Orescanin; Mark Merrifield; Sarah N. Giddings; Morgan C. Levy (Water Resources Research)
Abstract Saltwater intrusion (SWI) into coastal freshwater systems is a growing concern in the face of climate change‐driven sea level rise and hydrologic variability. Saltwater contamination of surface freshwater in the coastal California Pajaro Valley exemplifies this concern, where surface water cannot be diverted for agriculture if it is too saline. Closures at the mouth of the Pajaro River Lagoon, a bar‐built estuary in the Pajaro Valley, are associated with SWI. Closures and SWI are driven by a combination of offshore climate, coastal hydrodynamics, estuarine dynamics, inland hydrology, and infrastructure and management. Here, we describe the Pajaro Valley coastal water system and identify the oceanic and inland hydrologic drivers of SWI using available observational data between 2012 and 2020. We use time series and exploratory statistical analyses of coastal total water levels (TWLs), slough stage and salinity, river discharge, and contextual knowledge from local water managers. We observe that wet season lagoon closure and SWI events follow high oceanic TWLs coupled with low stage and discharge in the inland freshwater network, revealing how both wave and inland flow conditions govern lagoon closures and coincident SWI. This study yields novel empirical findings and a methodology for connecting coastal oceanography, estuarine coupled hydro‐ and morpho‐dynamics, inland hydrology, and water management practices relevant to climate change adaptation in human‐modified coastal water systems.